Role of calpain-5 in cerebral ischemia and reperfusion injury - Chukai, Yusaku; Ito, Ginga; Miki, Yasuo; Wakabayashi, Koichi; Itoh, Ken; Sugano, Eriko; Tomita, Hiroshi; Fukuda, Tomokazu; Ozaki, Taku (Biochimica et biophysica acta. General subjects, 2024)
Ischemia and reperfusion (I/R) injury exacerbate the prognosis of ischemic diseases. The cause of this exacerbation is partly a mitochondrial cell death pathway. Mitochondrial calpain-5 is proteolyzed/autolyzed under endoplasmic reticulum stress, resulting in inflammatory caspase-4 activation. However, the role of calpain-5 in I/R injury remains unclear. We hypothesized that calpain-5 is involved in ischemic brain disease. Mitochondria from C57BL/6J mice were extracted via centrifugation with/without proteinase K treatment. The expression and proteolysis/autolysis of calpain-5 were determined using western blotting. The mouse and human brains with I/R injury were analyzed using hematoxylin and eosin staining and immunohistochemistry. HT22 cells were treated with tunicamycin and CAPN5 siRNA. Calpain-5 was expressed in the mitochondria of mouse tissues. Mitochondrial calpain-5 in mouse brains was responsive to calcium earlier than cytosolic calpain-5 in vitro calcium assays and in vivo bilateral common carotid artery occlusion model mice. Immunohistochemistry revealed that neurons were positive for calpain-5 in the normal brains of mice and humans. The expression of calpain-5 was increased in reactive astrocytes at human infarction sites. The knockdown of calpain-5 suppressed of cleaved caspase-11. The neurons of human and mouse brains express calpain-5, which is proteolyzed/autolyzed in the mitochondria in the early stage of I/R injury and upregulated in reactive astrocytes in the end-stage. Our results provide a comprehensive understanding of the mechanisms underlying I/R injury. Targeting the expression or activity of mitochondrial calpain-5 may suppress the inflammation during I/R injuries such as cerebrovascular diseases.